Kasus “Sanding” antara Menantu Perempuan dengan Ibu Mertua yang Tinggal Serumah pada Masyarakat Batak Toba di Desa Situmeang Hasundutan Kecamatan Sipoholon Kabupaten Tapanuli Utara - Lenni E Situmeang; Jupalman W. Simbolon; Feriel Amelia Sembiring; Elvri T. Simbolon; Wensdy Sitindaon (Pusat Riset dan Inovasi Nasional, 2025)
The case of young couples at the beginning of marriage still choose to live in the same house with their parents, especially from the husband's side, so that the wife is also required to follow her husband to live with his parents, in this case the in-laws for the wife, so that it can trigger household problems that encourage the in-laws to interfere in it. This study aims to determine the type of interpersonal conflict between daughters-in-law and mothers-in-law who live in the same house in the Batak Toba tribe in Situmeang Hasundutan Village, Sipoholon District and the causes of